Wage inequality and returns to education in Turkey: A quantile regression analysis - Aysit Tansel; Fatma Bircan (Institute for the Study of Labor (IZA), 2010)
This paper investigates the male wage inequality and its evolution over the 1994-2002 period in Turkey by estimating Mincerian wage equations using OLS and quantile regression techniques. Male wage inequality is high in Turkey. While it declined at the lower end of the wage distribution it increased at the top end of wage distribution. Education contributed to higher wage inequality through both within and between dimensions. The within-groups inequality increased and between-groups inequality decreased over the study period. The latter factor may have dominated the former contributing to the observed decline in the male wage inequality over the 1994-2002. Further results are provided for the wage effects of experience, public sector employment, geographic location, firm size, industry of employment and their contribution to wage inequality. Recent increases in FDI inflows, openness to trade and global technological developments are discussed as contributing factors to the recent rising within-groups wage inequality.
Keywords: J31; J23; J24; I21; 330; wage inequality; returns to education; quantile regression; Turkey